Hydroxytyrosol and hypertension associated with chronic intermittent hypoxia: impact and contribution of AhR alternative pathway - Correia, Maria João Andrade (2023)
Abstract Chronic intermittent hypoxia (CIH) is the main clinical feature of obstructive sleep apnea (OSA), a highly prevalent chronic disease characterized by frequent episodes of upper airway collapse during sleep. CIH is currently recognized as the major factor responsible for the development of several cardiometabolic comorbidities associated with this pathology, namely arterial hypertension (HTN). In fact, the etiological connection between OSA and HTN is consensual, and OSA is now established as a type of secondary HTN. However, the pharmacological management of OSA-HTN is indistinguishable from essential HTN and the control of blood pressure (BP) with the current antihypertensive therapies in this particular type of HTN requires optimization. Thus, there is a need to identify new compounds able to better control blood pressure (BP) in this specific group of patients. The hypothesis underlying this thesis was strongly inspired in the beneficial cardiovascular effects of extra virgin olive oil, namely in its main phenolic compound hydroxytyrosol (OHTyr). We hypothesized that OHTyr represents a novel drug for the management of OSA-HTN by mechanisms involving redox changes in the thiolomic profile and in the AhR pathway. The thesis general goal was to investigate the effect of OHTyr in arterial HTN associated to CIH and the underlying mechanisms. For that, an animal model that mimics mild OSA (5.6 CIH cycles/h, 10.5 h/day during their inactive period) was used, as we were particularly interested in the earlier stages of OSA. At this stage, the use of continuous positive airway pressure (CPAP) as a preventive strategy for the onset of HTN is controversial and we were interested on investigating OHTyr as a putative alternative. OHTyr was administrated orally in a much higher dose than the present on olive oil, which safety profile was demonstrated by many other authors. We first characterized the variation of the cardiometabolic parameters (systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR)), body temperature (BT) and body weight (BW)) with the chronicity of IH, in order to better characterize the experimental model. This characterization was performed during the active (8 a.m.) and inactive (6 p.m.) periods of the animals, allowing to investigate the impact of CIH in circadian variation of the cardiovascular parameters, measured by radiotelemetry. In the paradigm used, CIH increased gradually both SBP and DBP and disrupted their circadian variation (Chapter I). To investigate the effect of OHTyr in the BP increased by CIH, a prevention and reversion protocols were designed. Oral administration of OHTyr (15 mg/Kg in refined olive oil) for 28 days prevented the increase in SBP induced by CIH in the active and inactive periods of animals by 70% and by 50%, respectively. This beneficial effect was not observed for DBP. Additionally, OHTyr was able to delay, but not to restore, the loss of dipper profile of BP induced by CIH. OHTyr did not change the BP in normoxic conditions (Chapter I). Encouraged by these preventive effects of OHTyr, we next performed a reversion protocol and observed that OHTyr administration (15 mg/kg in vegetable oil) for 14 days reverted the increase in both SBP and DBP induced by CIH by 93 ± 13% and by 59 ± 23%, respectively, in the active period of the animals. During the inactive period, when CIH stimuli was applied, neither SPB nor DBP were decreased by OHTyr administration (Chapter I). The study of the impact of CIH on OHTyr biotransformation, the main OHTyr metabolites were quantified in plasma samples by liquid chromatography coupled to tandem mass spectrometry (LC-MS) and revealed that CIH increased the levels of OHTyr sulfonated metabolites, namely OHTyr sulfate and homovanilic alcohol sulfate (Chapter I). Overall, we concluded that OHtyr is able to prevent and revert the increased BP associated to CIH in the active period of the animals, but at the dose investigate and administered before the inactive period it was not able to attenuate the disruption in the circadian variation of BP induce by CIH. Moreover, CIH impacts OHtyr biotransformation, which raises interesting possibilities for putative effects of OHTyr metabolites in BP control. Next, we aimed to investigate the interplay between aryl hydrocarbon receptor (AhR) and cysteine-related thiolomic profile at the kidney cortex, as both underlie the mechanisms of (mal)adaptation to CIH (Chapter II). We have also investigated the impact of the chronicity of IH in AhR activation and the thiolomic profile. We investigated the impact of short-term (1 and 7 days), mid-term (14 and 21 days, pre- HTN), and long-term IH (up to 60 days, established HTN) on CYP1A1 protein level (a sensitive hallmark of AhR activation) and cysteine-related thiol pools by Western blot and high-performance liquid chromatography with fluorescence detection (HPLCFD), respectively. We found that acute and chronic IH had opposite effects on CYP1A1 and the thiolome. While short-term IH decreased CYP1A1 and increased protein-Sthiolation, long-term IH increased CYP1A1 and free oxidized cysteine. Moreover, we performed an in vitro study employing different concentrations of cysteine and cystine in human umbilical vein endothelial cells (HUVECs). We observed that the administration of cystine, but not cysteine, increased Cyp1a1 gene expression, supporting cystine as a putative AhR activator. These results support CYP1A1 as a biomarker of OSA severity and oxidized pools of cysteine as risk indicator of OSA-HTN. Taking into account the relevance of cysteine and its different pools on AhR activation, we further investigated its tissue distribution (kidney cortex and medulla, liver, hippocampus and prefrontal cortex) under physiological conditions (Chapter III). We observed that the kidney, comparative to the liver or brain, is an organ particularly rich in cysteine. In the kidney, the total availability of cysteine was higher in cortex tissue than in the medulla and distributed in free reduced, free oxidized and protein-bound fractions (in descending order). Next, we provided a comprehensive integrated review on the evidence that supports the reliance on cysteine of the kidney, beyond its antioxidant properties. At last, we aimed to contribute to the knowledge about mechanisms underlying the impact of OHTyr in the control of the blood pressure. We performed pharmacometabolomic study to assess the pharmacological pathways of OHTyr under CIH conditions. The plasma samples from the animals of the reversion protocol were analyzed by LC-MS (Chapter IV). First, in an untargeted metabolomic analysis, we identified 2-aminophenyl sulfate as one of the metabolites responsible for the differences in the metabolomic profile between the CIH and CIH+OHTyr groups. In addition, in a targeted metabolomic approach, we observed that kynurenine and kynurenine-to-tryptophan ratio were also decreased upon OHTyr treatment. Overall, these results highlighted the putative disruption of tryptophan metabolism associated to CIH, which metabolites are well known activators of AhR. These findings suggest that the antihypertensive effect of OHTyr might be related to an attenuation of the AhR-CYP1A1 pathway. As we shown the interplay of AhR and the cysteine redox fractions, we hypothesized that OHTyr, which is well known by its antioxidants properties could also attenuate the changes in the thiolomic profile associated to CIH (Chapter IV). We have quantified the thiolomic profile (total availability of cysteine, glutathione and cysteinylglycine, as well as their reduced and oxidized pools) in kidney cortex and medulla tissues from animals of the reversion protocol in the early phase of inactive period, quantified by HPLC-FD methodology. CYP1A1 protein levels were also quantified in kidney cortex by Western blot to assess the effect of OHTyr in AhR activation. We observed that 35 days of CIH increased free oxidized cysteine fraction at kidney cortex and medulla and that OHTyr treatment was able to revert this increase in both tissues. OHTyr also increased protein cysteinylation in kidney medulla. Finally, OHTyr reverted the increase in CYP1A1 protein associated to CIH. This might suggest that OHTyr mechanism of action might also involve redox modulation of cysteine-related thiolomic profile that are might also be implicated in the regulation of AhR pathway. In conclusion, OHTyr might be responsible for the antihypertensive effects associated with olive oil consumption, since it prevents and reverts the CIH-induced increase in BP. This effect is evident on the active period of the animals. The attenuation of AhR pathway and regulation of the cysteine-related thiol pools in the kidney might represent mechanisms underlying this effect. Overall, the herein produced evidence contributes to a better understanding of the mechanisms underlying HTN associated to OSA and pave the way to the identification of molecules which might be risk indicators for the development of HTN in OSA. It also provides novel mechanisms for the cardiovascular friendly properties associated to Olive oil. Furthermore, it contributes to a better understanding of OHTyr pharmacology, and open perspectives for chronopharmacologic studies and putative actions of OHTyr metabolites and consolidates the AhR as putative therapeutic target for OSA-HTN.